De que forma a disciplina introdução às ciências biológicas pode ilustrar os campos de atuação do biólogo - Monteiro, Regina Teresa Rosim (Revista de Graduação USP, 2017)
The Introduction to Biological Sciences Discipline aims to show the studied object, its values and its characteristics. At the “Luiz de Queiroz” School of Agriculture, USP, Piracicaba, this compulsory course is offered in most courses. I have been in charge of this discipline since the creation of the course in Biological Sciences, in the year of 2002. During these fifteen years, I was able to follow the evolution of the disciplines offered for the graduation in Biological Science course and of the arriving students. At the end of the semester, in the evaluation of the student also includes in the questionnaire inquiries about evaluation of the discipline always leading to its improvement.